The Valproate Mediates Radio-Bidirectional Regulation Through RFWD3-Dependent Ubiquitination on Rad51 - Liu, Guochao; Lim, David; Cai, Zuchao; Ding, Wenwen; Tian, Zhujun; Dong, Chao; Zhang, Fengmei; Guo, Gongshe; Wang, Xiaowei; Zhou, Pingkun; Feng, Zhihui (Frontiers in Oncology, 2021)
Ionizing radiation (IR) can induce DNA double-strand breaks (DSBs) in tumor cells during radiotherapy (RT), but the efficiency of RT is limited because of the toxicity to normal cells. Locating an adjuvant treatment to alleviate damage in normal cells whilst sensitizing tumor cells to IR has attracted much attention. Here, using the 7,12-dimethylbenz[α]anthracene (DMBA)-induced malignant transformed MCF10A cells, we found that valproate (VPA), a histone deacetylase inhibitor (HDACi), radiosensitized transformed cells while alleviated IR-induced damage in normal cells at a safe dose (0.5mM). We further demonstrated the decrease of homologous recombination (HR)-associated Rad51 in the transformed cells was related to the increase of its ubiquitination regulated by E3 ligase RFWD3 for the radiosensitization, which was opposite to normal cells, indicating that RFWD3-dependent ubiquitination on Rad51 was involved in the VPA-mediated radio-bidirectional effect. Through DMBA-transformed breast cancer rat model, VPA at 200mg/kg radiosensitized tumor tissue cells by increasing RFWD3 and inhibited Rad51, whilst radioprotected normal tissue cells by decreasing RFWD3 and enhanced Rad51. In addition, we found high-level Rad51 was associated with tumorigenesis and poor prognosis in breast cancer patients. Our findings uncovered RFWD3-dependent Rad51 ubiquitination was the novel mechanism of VPA-mediated radio-bidirectional effect, VPA is a potential adjuvant treatment for tumor RT.